Electromechanical delay by speckle-tracking echocardiography: A novel tool to distinguish between Brugada syndrome and isolated right bundle branch block. (1st December 2020) - D'Ascenzi, Flavio; Sanz-De La Garza, María; Anselmi, Francesca; Nunno, Loredana; Arbelo, Elena; Jordà, Paloma; Marzotti, Tommaso; Aprile, Federica; Piu, Pietro; Natali, Benedetta Maria; Brugada, Josep; Sitges, Marta; et al.
Abstract: Background: The electrocardiographic (ECG) definition of Brugada syndrome (BS) can be challenging because benign ECG abnormalities, such as right bundle branch block (RBBB), may mimic pathological ECG characteristics of BrS. However, although myocardial delay and deformation can be quantified by advanced imaging, it has not yet been used to differentiate between BrS and RBBB. The aim of this study was to characterize the electro-mechanical behavior of the heart of patients with type-1 BrS and isolated complete RBBB in order to differentiate these conditions. Methods: In this two-center study, 66 subjects were analyzed by standard and speckle-tracking echocardiography (STE): 22 type-1 BrS, 24 isolated complete RBBB, and 20 healthy subjects. The participants were not treated by any drug potentially influencing myocardial conduction. Results: Standard echocardiographic parameters did not differ among the groups. The greatest right ventricular (RV) mechanical dispersion was found in RBBB. Mean absolute deviations (MADs) of time-to-peak longitudinal strain calculated for each left ventricular (LV) region were greater in patients with RBBB as compared to BrS ( p < .01). No differences were found between BrS and controls ( p = .36). MADs in the basal segments in RBBB group were greater than MADs found in BrS group and controls (37.3 ms vs. 26.7 ms and 29.0 ms, respectively, p < .05). The greatest differences were found in the antero-septal, anterior, lateral, and infero-septal basal segments. Conclusions: Advanced echocardiographic techniques may help to differentiate between BrS and RBBB. Indeed, STE allows to identify an electro-mechanical conduction delay in RBBB patients that is not found in patients affected by type-1 BrS. Highlights: Standard echocardiography did not differ between RBBB and BrS. In RBBB mechanical dispersion is greater than type1-BrS patients. The greatest degree of dispersion is observed in LV basal segments. Mechanical dispersion helps distinguishing between RBBB and type-1 BrS.